2006
DOI: 10.1159/000095732
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Ambiguous Idiomatic Statements in Schizophrenic and Depressive Patients. Evidence for Common and Differential Cognitive Patterns

Abstract: Background: This study is concerned with the comprehension of ambiguous idiomatic statements in schizophrenic and depressive patients. Aims: Using a multiple-choice procedure, we simultaneously tested the presence of concrete and literal elements in the understanding of idiomatic statements. Method: Fourteen schizophrenic and 10 patients undergoing a major depressive episode as well as 14 control subjects completed a questionnaire with 10 idiomatic expressions with two possible interpretations (figurative and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 86 publications
3
8
0
Order By: Relevance
“…Furthermore, unusual associations have been reported [69], as well as abnormalities in processing sentential ambiguity. In line with our model, both latter abnormalities appear to result from reduced sensitivity to context and a preference for the dominant meaning of polysemic words [70][72]. An extensive review [73] concluded that language competence appears to be intact in schizophrenia, and that the language problems reflect more general problems in information processing.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, unusual associations have been reported [69], as well as abnormalities in processing sentential ambiguity. In line with our model, both latter abnormalities appear to result from reduced sensitivity to context and a preference for the dominant meaning of polysemic words [70][72]. An extensive review [73] concluded that language competence appears to be intact in schizophrenia, and that the language problems reflect more general problems in information processing.…”
Section: Discussionsupporting
confidence: 80%
“…SZ patients have been reported to be more impaired in comprehending non-literal than literal language since early studies on proverbs and metaphors (Gorham, 1961 ; Kasanin, 1994 ). Impairment in the comprehension of non-literal language continues to be documented in terms of preference for literal rather than figurative interpretations and poor appreciation of irony ( literality bias ) (metaphors: Chapman, 1960 ; Cutting and Murphy, 1990 ; Spitzer, 1997 ; Drury et al, 1998 ; Langdon et al, 2002 ; Langdon and Coltheart, 2004 ; Kircher et al, 2007 ; Mashal et al, 2013 ; idioms: Titone et al, 2002 ; Iakimova et al, 2005 , 2006 , 2010 ; Schettino et al, 2010 ; proverbs: Gorham, 1961 ; de Bonis et al, 1997 ; Sponheim et al, 2003 ; Brüne and Bodenstein, 2005 ; Kiang et al, 2007 ; Thoma et al, 2009 ; irony: Herold et al, 2002 ; Langdon et al, 2002 ; Rapp et al, 2013 ).…”
Section: Deficits In the Comprehension Of Non-literal Language In Szmentioning
confidence: 99%
“…Impaired figurative language comprehension has also been linked to inadequate use of contextual information to construct abstract figurative meanings (Strandburg et al, 1997 ; Kircher et al, 2007 ). However, Titone et al ( 2002 ; see also Iakimova et al, 2006 , 2010 ) questioned the idea that SZ patients necessarily exhibit a literality bias. In fact, the lexical decision study of Titone et al showed that SZ patients were as able as control subjects to use idiomatic contexts to generate idiomatic interpretations when the idiomatic meaning was literally implausible (e.g., come up roses ) but they instead failed when the idiomatic meaning was semantically ambiguous having also a literal counterpart (e.g., break the ice ).…”
Section: Deficits In the Comprehension Of Non-literal Language In Szmentioning
confidence: 99%
“…Normally, the contextual constraints in communications bias listeners towards figurative interpretations of idioms. However, patients with schizophrenia often opt for the literal interpretation (Iakimova et al, 2006). It is as if people with schizophrenia seem to expect the literal meaning of ambiguous idioms, unless they are almost invariably used in a figurative manner (Schettino et al, 2010).…”
Section: And Michal Lavidormentioning
confidence: 99%